2002
DOI: 10.1128/jb.184.15.4233-4239.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Murein Precursor UDP- N -Acetylmuramyl- l -Ala-γ- d -Glu- meso -Diaminopimelic Acid- d -Ala- d -Ala in Repression of β-Lactamase Induction in Cell Division Mutants

Abstract: Certain ␤-lactam antibiotics induce the chromosomal ampC ␤-lactamase of many gram-negative bacteria. The natural inducer, though not yet unequivocally identified, is a cell wall breakdown product which enters the cell via the AmpG permease component of the murein recycling pathway. Surprisingly, it has been reported that ␤-lactamase is not induced by cefoxitin in the absence of FtsZ, which is required for cell division, or in the absence of penicillin-binding protein 2 (PBP2), which is required for cell elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
5
13
0
Order By: Relevance
“…The consequence of this may be that although the production of the AmpR-activating molecule 1,6-anhydromuropeptide has been blocked, the disruption of PG recycling may not allow the mutant to sustain sufficient cytoplasmic concentrations of UDP-MurNAc pentapeptide to fully repress AmpR. Consistent with this view, the suppression of inducible ␤-lactamase resistance has been observed in cell division mutants that accumulate cytosolic UDP-MurNAc pentapeptide, presumably because increased amounts of the molecule outcompete the incoming anhydromuropeptide inducer and ensure the continued repression of AmpR (45). Regardless, further studies will be required to clarify the precise molecular roles of these inducer and repressor molecules.…”
Section: Discussionsupporting
confidence: 65%
“…The consequence of this may be that although the production of the AmpR-activating molecule 1,6-anhydromuropeptide has been blocked, the disruption of PG recycling may not allow the mutant to sustain sufficient cytoplasmic concentrations of UDP-MurNAc pentapeptide to fully repress AmpR. Consistent with this view, the suppression of inducible ␤-lactamase resistance has been observed in cell division mutants that accumulate cytosolic UDP-MurNAc pentapeptide, presumably because increased amounts of the molecule outcompete the incoming anhydromuropeptide inducer and ensure the continued repression of AmpR (45). Regardless, further studies will be required to clarify the precise molecular roles of these inducer and repressor molecules.…”
Section: Discussionsupporting
confidence: 65%
“…Impairment of PBP2 activity leads to spherical cells in which peptidoglycan is largely confined to the septum (18), which may limit peptidoglycan recycling (72). Consistent with this, the evolved pbpA alleles reduce PBP2 levels while also generating spherical cells.…”
Section: Discussionsupporting
confidence: 49%
“…In an Escherichia coli mpl mutant, a 1.7-fold decrease in the level of the UDP-MurNAc-pentapeptide pool was observed compared to the wild type (23). In Citrobacter freundii, in vitro transcription assays demonstrated that this murein precursor acts as a repressing ligand for AmpR (57). It has been suggested that a similar situation might occur in P. aeruginosa (32,40).…”
Section: Resultsmentioning
confidence: 86%